RESTRIÇÃO DE CRESCIMENTO INTRAUTERINO (RCIU) COMO PARTE DA SÍNDROME ALCOÓLICA FETAL - Olguin Calvillo, Jose Antonio; Delgadillo Aldana, Julieta Belen; Arteaga Vazquez, Brenda Abigail; Guerra Cárdenas, José Eugenio (Brazilian Medical Students, 2024)
Introduction: An investigation was conducted on the effects of alcohol on pregnant women as a possible cause of intrauterine growth restriction. The American Pregnancy Association defines intrauterine growth restriction (IUGR) as a fetal weight below the 10th percentile for gestational age as determined by ultrasound. Method: A search of medical literature was performed from January 2010 to January 2022. For this purpose, different scientific databases were used, which were: PUBMED, EBSCO and Google Scholar. Results: The fetal period is the time of development from the ninth week to the moment of birth. The most severe form associated with alcohol consumption during pregnancy is Fetal Alcohol Syndrome, which requires a minimum consumption of 12 g per day of absolute alcohol for this syndrome to manifest itself. Infants whose mothers are chronic alcoholics show a characteristic pattern of defects including prenatal and postnatal growth deficiencies, mental deficiency, and other problems. Discussion: Environmental factors influence fetal growth, and this has been increasingly emphasized with increasing evidence. With regard to the database collected from different research sources, we can confirm the great relationship that exists on the effects of alcohol consumption by pregnant women on fetal growth. Kazutoshi-cho's study on prenatal exposure to alcohol in Japanese women shows us that the consumption of a weekly dose of alcohol during the second and third trimester has a significant negative relationship with the decrease in body weight, body length and head circumference at birth. Conclusion: Excessive alcohol consumption is highly associated with fetal growth restriction (fetal alcohol syndrome). The level of effects may be different depending on the frequency of exposure and dose.